Auditory studies of spotted and ringed seals: Amphibious hearing and the effects of noise - Sills, Jillian Marie (eScholarship, University of California, 2016)
The auditory biology and acoustic behavior of Arctic seals are incompletely understood, in large part due to the significant challenges of studying ice-living seals in natural habitats. Consequently, many questions regarding their perception of acoustic cues in the marine environment, and the ways in which increasing anthropogenic noise may influence their ability to detect biologically relevant sounds, remain unanswered. This dissertation describes a series of behavioral studies conducted in the laboratory to characterize the auditory capabilities of trained spotted (Phoca largha, Pallas 1811) and ringed seals (Pusa hispida, Schreber 1775) in quiet conditions, in the presence of controlled noise, and in real-world listening scenarios. The first two chapters comprise a set of three standard audiometric studies for each species, including aerial audiograms, underwater audiograms, and critical ratio measurements in both media. The results presented in Chapter 1 are the first hearing data available for spotted seals, and provide insight into the acoustic ecology of this minimally studied species. The results presented in Chapter 2 are the most comprehensive hearing data available thus far for ringed seals, and offer an updated perspective on the auditory capabilities of this species relative to historical data. Chapter 3 builds upon these standard examinations of hearing to investigate auditory performance in more complex acoustic environments—specifically, habitats altered by seismic noise from geophysical exploration. Taken together, these experiments provide fundamental knowledge about the sensory biology of spotted and ringed seals, which can be applied to management decisions for these species in an increasingly human-influenced Arctic environment.